KONFLIK INTERNAL PARTAI NASDEM DAN PEMILIHAN LEGISLATIF 2014 - Diana, Yunicha; Kurniawan, Robi Cahyadi (JWP (Jurnal Wacana Politik), 2016)
After election commission passed Nasdem Party to participate in the 2014 elections, the party is now headed by Surya Paloh reap discord. The split was marked by the release of Hary Tanoe Soedibjo, Chairman of the Board of Expert Nasdem Party. Hary Tanoe addition, Secretary-General Ahmad Rofik, Saiful Haq Deputy Secretary-General, and the Chairman of the Internal DPP Nasdem Tirtana Endang also resigned from the party Nasdem. The resignation was caused by disagreement with Surya Paloh who plans to overhaul the management of board center. The purpose of this study was to determine the internal conflict and branding of Nasdem Political Party In Legislative Election Year 2014. The result shows Nasdem internal conflict as a conflict of interest due to the race for Chairman Nasdem between Surya Paloh and Hary Tanoe Sudibjo. This conflict resulted the resignation Hary Tanoe and followed by Nasdem cadres in several regions in Indonesia. Nasdem administrators in several regions in Indonesia who resigned are the supporters of Hary Tanoe. Impact in the community is its lack of public confidence in Nasdem as new party that is expected to bring positive change so that this conflict can interfere with imaging Nasdem the 2014 Elections.